2013
DOI: 10.1007/s11103-013-0150-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of the microRNA transcriptome of a moth orchid Phalaenopsis aphrodite

Abstract: Orchids display unique phenotypes, functional characteristics and ecological adaptations that are not found in model plants. In this study, we aimed to characterize the microRNA (miRNA) transcriptome and identify species- and tissue-specific miRNAs in Phalaenopsis aphrodite. After data filtering and cleanup, a total of 59,387,374 reads, representing 1,649,996 unique reads, were obtained from four P. aphrodite small RNA libraries. A systematic bioinformatics analysis pipeline was developed that can be used for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 72 publications
1
24
0
Order By: Relevance
“…Moreover, we have added RNA-Seq based gene expression data for 65 tissues/developmental stages. For the pre-existing orchid miRNA (Chao et al 2014) and microarray information (Su et al 2013b), all of the newly generated RNA-Seq transcriptome data were integrated and consistency was ensured. The orchid species and tissues were selected to cover the evolutionary classification of orchids and to be relevant to orchid breeders and researchers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we have added RNA-Seq based gene expression data for 65 tissues/developmental stages. For the pre-existing orchid miRNA (Chao et al 2014) and microarray information (Su et al 2013b), all of the newly generated RNA-Seq transcriptome data were integrated and consistency was ensured. The orchid species and tissues were selected to cover the evolutionary classification of orchids and to be relevant to orchid breeders and researchers.…”
Section: Resultsmentioning
confidence: 99%
“…Orchid genomes are typically larger than those of most model plants and there is remarkable variability in genome size across the family, with the amount of nuclear DNA varying up to 168-fold (Leitch et al 2009). Most of the effort in sequencing orchid species is being made using transcriptome sequencing (Su et al 2011, Tsai et al 2013, Zhang et al 2013, Chao et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…An integrated database, Orchidstra, has recently been constructed (http://orchidstra.abrc.sinica.edu.tw/; Su et al, 2013a). The Orchidstra database contains transcriptome information for five orchid species and one commercial hybrid as well as microRNA (Chao et al, 2014) and microarray-based expression profiling data for a potential orchid model species, P. aphrodite (Su et al, 2013b). Transcriptome analysis of Cymbidium using Illumina sequencing has been reported from China Zhang et al, 2013b).…”
Section: Orchidsmentioning
confidence: 99%
“…48 miR5021 was also reported in a few plant species such as peach, ginseng, sunflower, radish, longan, Jatropha curcas, moth orchid, Brassica oleracea, and Arabidopsis. 24,26,[49][50][51][52][53][54] It was indicated that miR5021 families may be involved in the regulation of lipid metabolism and responses to stress, and MYB proteins and SPL3 transcription factor may be the target of miR5021. 26 Although miR156-3p, miR1522, miR5658, miR5783, and miR5998 were also identified in other species, their functional roles remain unknown as yet.…”
Section: Characterization Of Potential Mirnas In Blueberrymentioning
confidence: 99%